Economic and Financial Impact of the Covid-19 Pandemic on the Insurance Market in Albania, Serbia and Northern Macedonia: Array - Koci, Ervin; Hoxha, Valter; Bombaj, Florjan; Haderi, Sulo (Acta Universitatis Danubius. Œconomica, 2021)
As in many parts of the world, the Covid-19 sanitary pandemic has hit very hard the economies hard in the of the countries of the Western Balkans. The economy faced a “shock” both on the supply and on the demand. Most economic sectors were paralyzed. One of these sectors is the insurance market, which represents a relatively important weight for the economic and financial sector. The purpose of this article is to show the impact of Covid-19 on the insurance market in the three countries of the Western Balkans: Albania, Serbia and Northern Macedonia. Based on the specifics of this crisis and particularly that of the insurance sector, the purpose of this article is to verify the impact of Covid-19 on the insurance market and specifically, on the volumes of gross annual premiums. To verify it, we have analyzed the annual data of this sector, before the pandemic and throughout the pandemic. The results show that the Covid-19 pandemic for Albania and Macedonia has had a negative impact on the market of this sector, while for Serbia we have an increase in the annual data.